INSTRUMENTS FOR ASSESSING SLEEP IN ADOLESCENTS: BRAZILIAN LITERATURE'S REVISION. (Fiep Bulletin - online, 2016)
Introduction: sleep has a vital role in the human being's survival and it has diverse functions. Poor sleep conditions clearly intervene in a person's quality of life and it can also generate sleep disorders. The aftereffects of sleep disorders in human beings are negative. They influence quality of life, autonomic dysfunction, academic and professional performance, among others. Adolescents, particularly college students, don't always have healthful sleep habits. A large number of adolescents have less sleep than their physiological and cognitive needs. Objective: To assess the instruments of sleep analysis in Brazilian adolescents. Method: scientific articles in the SCIELO and LILACS databases were searched, the inclusion criterion was the year of publication (2010-2015) and the approach was directed to the subject. Duplicate articles were excluded. Results: initially, 102 articles were found, in which 10 fulfilled the criterion. Conclusion: the analysis of the most recent studies made in Brazil show predominance of the use of the evaluation instrument PSQI (Pittsburgh Sleep Quality Index) in five of the studies analyzed, which indicates a possible standard in the Brazilian research.
Keywords: sleep disorders; instruments; adolescents.